2018
DOI: 10.18632/oncotarget.25505
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of metal response element binding transcription factor 2 at the Hox gene cluster in the regulation of H3K27me3 by polycomb repressive complex 2

Abstract: Polycomb repressive complex 2 (PRC2) is known to play an important role in the regulation of early embryonic development, differentiation, and cellular proliferation by introducing methyl groups onto lysine 27 of histone H3 (H3K27me3). PRC2 is tightly associated with silencing of Hox gene clusters and their sequential activation, leading to normal development and differentiation. To investigate epigenetic changes induced by PRC2 during differentiation, deposition of PRC2 components and levels of H3K27me3 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…inhibitors might lead to decreased H3K27me3 at HOX loci, potentially leading to their overactivation. Nonetheless, Khan et al [193] recently demonstrated that, in opposition to the classical view that PRC2 is the major transcriptional repressive complex of HOX genes, the knockdown of some PRC2 subunits, such as SUZ12, EZH2, or EED, in mouse F9 teratocarcinoma cells, globally decreased H3K27me3 levels, but not in HOX clusters, where curiously H3K27me3 increased instead.…”
Section: Clinical Implications Of Hox Genesmentioning
confidence: 94%
See 1 more Smart Citation
“…inhibitors might lead to decreased H3K27me3 at HOX loci, potentially leading to their overactivation. Nonetheless, Khan et al [193] recently demonstrated that, in opposition to the classical view that PRC2 is the major transcriptional repressive complex of HOX genes, the knockdown of some PRC2 subunits, such as SUZ12, EZH2, or EED, in mouse F9 teratocarcinoma cells, globally decreased H3K27me3 levels, but not in HOX clusters, where curiously H3K27me3 increased instead.…”
Section: Clinical Implications Of Hox Genesmentioning
confidence: 94%
“…Indeed, although decreased enrichment of the PRC2 complexes was observed at HOX loci upon SUZ12, EZH2, or EED silencing, the expression of HOX genes did not increase [193]. MTF2 was pointed as the potential responsible molecule for H3K27me3 enrichment in HOX loci in the absence of PRC2 [193]. Whether a similar effect and underlying mechanism is more generally observed in cancer, including in GBM, remains to be investigated.…”
Section: Clinical Implications Of Hox Genesmentioning
confidence: 98%
“…Importantly, even when only genes with significant RNAseq changes ( p val < 0.05, |Log2FC|> 1) were visualized (red dots in Supplemental Figure S5 ) it became apparent that more genes with a significant increase in H3K27me3 showed an increase in mRNA levels (65) versus those that demonstrated reduced expression (48). Collectively, these results indicate there is little direct correlation between the deposition of H3K27me3 and gene expression, as has been seen in other situations 44 46 . While DOT1L inhibition does revert the transcriptome of cohesin heterozygous cells to a more WT state (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…ZIPs have 14 members that facilitate an increase in the cytosolic concentration of Zn 2+ ( 73 ). Metal regulatory transcription factor 1 (MTF-1) is sensitive to Zn 2+ and activated via cysteine2-histidine2 (Cys2-His2) Zn fingers binding to DNA to mediate the expression of ZnT1, ZnT2, and metallothioneins (MTs), which regulate the storage and release of intracellular Zn 2+ ( 74 , 75 ) ( Figure 1 ).…”
Section: Metal Ions In Anti-cancer Immunitymentioning
confidence: 99%